Analisis Pelaksanaan Pembelajaran Dengan Metode Sorogan di TPQ Al-Mujahidin Perum Purnamandala Bumireso Wonosobo Terhadap Kemampuan Membaca Al-Qur’an Santri - Aulida Yuni Rachmawati; Ahmad Zuhdi; Salis Irvan Fuadi (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2024)
Al-Qur'an is a holy book revealed by Allah SWT. to Prophet Muhammad SAW. as guidance for believers and the pious. It was sent down to be studied and understood by mankind, providing tranquility and beneficial knowledge in life. The purpose of this research is to investigate the implementation of the “sorogan” method in the Islamic education center TPQ Al-Mujahidin. Additionally, it seeks to assess the proficiency of students’ Qur’anic recitation proficiency among students before and after the implementation of the sorogan method. It is essential to identify factors influencing the effectiveness of the sorogan method in Qur’anic education is also crucial. This study adopts a quantitative research approach, which is characterized by a systematic, scheduled, and clearly structured process from the initial design to the final presentation of results. Quantitative research involves gathering numerical data, interpreting it, and concluding with presenting the findings. The research was conducted at TPQ Al-Mujahidin, Perum Purnamandala, involving male and female students as research subjects. A comprehensive conclusion is enhanced by visual aids such as graphs, tables, diagrams, and other visual presentations. The findings of this study are as follows, First the sorogan method has been implemented for a considerable duration at TPQ Al-Mujahidin. According to the TPQ head, teaching at TPQ using the sorogan method focuses on the teacher. Educators explain the substance of the lesson to students, who listen attentively. Subsequently, students apply what they have learned during their recitations. Second, the proficiency of Qur'anic recitation among students can be evaluated through various aspects, including fluency (fashohah), understanding of tajwid rules, comprehension of ghorib rules, and knowledge of makhorijul huruf. Additionally, students’ recitation abilities are influenced by their motivation and interest in reading the Qur’an. These reading skills are significantly affected by the method of instruction and its application in the learning process. Third, factors affecting the effectiveness of the sorogan method on Qur’anic recitation proficiency in Qur’anic recitation, readiness/teaching techniques of the teacher, and students motivation. In conclusion, the sorogan method, despite its longevity and focus on teacher-centered learning, impacts students’ ability to recite the Qur’an effectively. Enhancing preparation, refining teaching techniques, and fostering students motivation are crucial for optimizing the effectiveness of this method in Qur’anic education Keywords: , , ,